The competences to conduct the profile of student pancasila in islamic junior secondary school - Musdalifa; Aminullah; Fatimah (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2024)
This research aims to explore the competences required for teachers to conduct the profile of Student Pancasila in Islamic Junior Secondary Schools and to understand how these competences influence the implementation and internalization of Pancasila values among students. With Pancasila being the guiding philosophy of Indonesia, encapsulating values of belief in the One and Only God, just and civilized humanity, Indonesian unity, representative democracy, and social justice, it is imperative to examine the role of teacher competences in fostering these principles. The study adopts a descriptive approach to investigate the relationship between teacher competence—including pedagogic, professional, personality, and social competences—and students' understanding of Pancasila. Data were collected through observations, interviews, and documentation, with analysis following Miles and Huberman's interactive model. Findings suggest that pedagogic competence, particularly effective communication and evaluation skills, is crucial for nurturing Pancasila values. Professional competence, including subject matter mastery and the integration of technology, enhances the relevance of teaching Pancasila. Personality competence, with an emphasis on role modeling, and social competence, focusing on inclusive and empathetic communication, are found to be influential in the values internalization process. The study concludes that a holistic approach to teacher competence is vital for the successful impartation of Pancasila values, which is fundamental for building students' character in alignment with the Indonesian state ideology. Recommendations are made for curriculum development and teacher training programs to support this endeavor.